Food security: Where are we heading? - Fakhrul Anwar, Zainol; Nalini, Arumugam; Aik, Chua Kim (2015)
The issues of food security are an important aspect of every country for its social and economic growth and the eradication of poverty. It is particularly crucial for satisfying the needs of the ever-growing population in developing countries. Agriculture is the backbone of the people and the economy for developing countries, particularly in highly populated countries such as India, China and South East Asia. The world population is anticipated to rise to 8.3 billion by 2030 and to 9.2 billion by 2050. By that time, to feed the growing population, food production must double to keep pace with the escalating food demand. Agricultural commodities showed increases of 58.9% in import dependency ratio (IDR) as compared to 32.2% in 2013. Thus, this study attempts to review and explore the challenges of food security as well as the opportunities of the seed industry in Malaysia.